A Review on the Capacities of the ISO/IEC/IEEE 42020:2019 Standard for Architecture Elaboration of Software and Systems - Costa, José Eduardo Chaves; Soares, Michel dos Santos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
Context: Software architecture is useful for managing elements such as software, data, business functions, services, hardware, and stakeholders with their viewpoints, concerns, constraints, and requirements. One solution for describing software architectures is the ISO/IEC/IEEE 42020 standard, which standardizes the processes of management and description of an architecture or a collection of architectures. Problem: However, it is common for developers, architects, or companies to face difficulties in developing the architecture processes specified in the ISO/IEC/IEEE 42020 standard. As a consequence, these professionals tend to look for improvised ways to describe their architecture. IS Theory: This study was developed under the aegis of the General Systems Theory, focusing on the relationships between the elements that form the software architecture. Methods: The study was developed under the qualitative paradigm and exploratory bias. The main object of study is the ISO/IEC/IEEE 42020 standard and its processes. Summarization of the Results: The study presented concepts, principles, and theories related to the use of the architecture processes described in the ISO/IEC/IEEE 42020 standard. The goal is to help developers to understand and make better decisions about the management and description of a software architecture. Contributions and Impact in the IS area: The results of this study provide valuable insights into the understanding, learning, and interpretation of the ISO/IEC/IEEE 42020 standard, allowing for the structure of efficient architectural practices in the construction of software.